Pengaruh Penggunaan Starter Bakteri Asam Laktat Lactobacillus plantarum dan Lactobacillus fermentum terhadapTotal Bakteri Asam Laktat, Kadar Asam dan Nilai pH Dadih Susu Sapi - Afriani, Afriani (Fakultas Peternakan Universitas Jambi, 2010)
The objective of the current study to determine the effect of the use of bacteria Lactobacillus plantarum and Lactobacillus fermentum in the manucfacture of cow’s milk curd on the total lactid acid bacteria, acidity and pH value of cow’s milk curd. The experiment use fresh cow milk and starter culture of Lactobacillus plantarum, and L. plantarum. Starter culture added about 3% from milk volume than incubated at room temperature during 48 hours. The treatments were fermentation with L. plantarum (A1); L. fermentum (A2); L. plantarum + L. fermentum (A3). There were significant effect of addition of starter L. plantarum (A1), L. fermentum (A2), and the combination of L. plantarum + L. fermentum (A3) on total lactic acid bacteria and acidity, however, there was no statistically significant on the pH value of cow's milk curd. It was concluded that using of starter culture combinations of Lactobacillus plantarum + Lactobacillus fermentum (A3) increases the total lactic acid bacteria and acid levels of cow’s milk curd.